Diabetes and Heart Failure: Multi-Omics Approaches - Tayanloo-Beik, Akram; Roudsari, Peyvand Parhizkar; Rezaei-Tavirani, Mostafa; Biglar, Mahmood; Tabatabaei-Malazy, Ozra; Arjmand, Babak; Larijani, Bagher (Frontiers in Physiology, 2021)
Diabetes and heart failure both as noticeable global issues, cause much expenses to the countries and medical systems considering morbidity and mortality rates. Majority of diabetics suffer from type 2 which has an amplifying effect on the prevalence and severity of many health problems such as stroke, neuropathy, retinopathy, kidney injuries, and cardiovascular disease. Diabetes type 2 is one of the cornerstones of heart failure, another health epidemic, with the prevalence of 44%. Accordingly, finding and targeting specific molecular and cellular pathways involved in the pathophysiology of each disease, either in diagnosis or treatment, will be beneficial. Coming to diabetic cardiomyopathy, there are several mechanisms through which clinical heart failure is developed, oxidative stress with the mediation of Reactive Oxygen Species (ROS), reduced myocardial perfusion due to endothelial dysfunction, autonomic dysfunction as well as metabolic changes such impaired glucose levels caused by insulin resistance are four main mechanisms. In the field of oxidative stress, Advanced Glycation End products (AGEs), Protein kinase C (PKC), and Nuclear Factor Kappa-light-chain-enhancer of activated B cells (NF-κB) are the involved mediators which new omics-driven methods can target. Besides, diabetes can affect myocardial function through impairing ca homeostasis, the mechanism in which reduced Protein Phosphatase 1 (PP1), the Sarcoplasmic/Endoplasmic Reticulum Ca2+ ATPase 2a (SERCA2a), and phosphorylated SERCA2a expression are main effectors. In this article we are going to have a review of the recent omics-driven discoveries in the diagnosis and treatment of diabetes type 2 and heart failure with the focus on the common molecular mechanisms.